3D creep cavitation characteristics and residual life assessment in high temperature steels: a critical review. (March 2015) - Gupta, C.; Toda, H.; Mayr, P.; Sommitsch, C.
<x content-type="archive" xml:space="preserve">Abstract</x> The need for a new paradigm to estimate remaining creep life of service exposed steels is critically assessed. New approaches to residual life assessment are proposed, in the light of a decade's experience of the use of micro-tomography to characterise the three-dimensional (3D) nature of cavitation damage in structural materials. Imaging of conventional structural materials such as steels with high absorption to X-rays has been realised by synchrotron micro-tomography (SR-μCT), providing new insights into phenomena such as creep failure. The unique feature of SR-μCT studies is the direct imaging in 3D of cavities (hundreds of micrometres in size) present in the bulk, revealing the spatial characteristics and morphology of the creep voids. Quantitative analyses of the cavitation characteristics revealed by 3D datasets, when scaled with respect to time, stress and temperature, provide functional information suitable for developing constitutive equations for creep. The application of SR-μCT, a non-destructive technique providing high fidelity data, significantly reduces the ambiguity in developing functional relationships to predict creep failure. The explicit use of such constitutive equations to estimate the residual life of components in creep, and the consequent assessment of structural integrity, would prove invaluable. Micro-tomography studies related to creep in materials are reviewed, with special emphasis on a 10·86%Cr heat resistant steel, to demonstrate the type of data available for life assessment and design against creep failure. A brief discussion of current methods to estimate residual life in the light of recent 3D micro-tomography data follows. Finally, the possibility of new approaches, using micro-tomography data in conjunction with destructive 3D approaches such as serial sectioning, to formulate advanced residual life estimates, is briefly considered.